Reduced pituitary size in subjects with mutations in the THRB gene and thyroid hormone resistance. Issue 1 (19th January 2022) - Heldmann, Marcus; Chatterjee, Krishna; Moran, Carla; Rogge, Berenike; Steinhardt, Julia; Wagner-Altendorf, Tobias; Göttlich, Martin; Schacht, Hannes; Schramm, Peter; Brabant, Georg; Münte, Thomas F; Cirkel, Anna
Abstract : Background: Thyroid hormone action is mediated by two forms of thyroid hormone receptors (α, β) with differential tissue distribution. Thyroid hormone receptor β (TRβ) mutations lead to resistance to thyroid hormone action in tissues predominantly expressing the β form of the receptor (pituitary, liver). This study seeks to identify the effects of mutant TRβ on pituitary size. Methods: High-resolution 3D T1-weighted magnetic resonance images were acquired in 19 patients with RTHβ in comparison to 19 healthy matched controls. Volumetric measurements of the pituitary gland were performed independently and blinded by four different raters (two neuroradiologists, one neurologist, one neuroscientist). Results: Patients with mutant TRβ (resistance to thyroid hormone β, RTHβ) showed elevated free tri-iodothyronine/thyroxine levels with normal thyroid-stimulating hormone levels, whereas healthy controls showed normal thyroid hormone levels. Imaging revealed smaller pituitary size in RTHβ patients in comparison to healthy controls (F(1, 35) = 7.05, P   = 0.012, partial η 2  = 0.17). Conclusion: RTHβ subjects have impaired sensitivity to thyroid hormones, along with decreased size of the pituitary gland.